PENERAPAN VALUE FOR MONEY UNTUK MENILAI KINERJA DINAS PERKEBUNAN PROVINSI SULAWESI UTARA - Karwur, Andre Hendry; Ilat, Ventje; Pinatik, Sherly (Universitas Sam Ratulangi, 2014)
The Plantation is one of the basic needs supporting of human. Plantation development in North Sulawesi implemented with resource management and maintenance. So with this duties and responsibilities by the government, in this case Department of Plantation of North Sulawesi Province is more. The purpose of this research was to determine the financial performance of the Department of Plantation of North Sulawesi Province, through the measurement of 3E (economy, efficiency, and effectiveness). In this research, measurement of economic value is using interview techniques, efficiency value is using the ratio of output and input value from data LAKIP of Department of Plantation of North Sulawesi Province, while the value is calculated based on comparison of outcomes and outputs value, where the outcome shows the level of community satisfaction obtained from the questionnaires to the people of North Sulawesi Province. The results of this research indicate that the economy and efficiency value of the Department of Plantation of North Sulawesi Province Department of Plantation of North Sulawesi Province were able to achieve fairly good results. But, the level of effectiveness is still lacking, because it is based on the level of community satisfaction that is not maximized.